1978
DOI: 10.1161/01.res.42.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics of coronary artery stenosis.

Abstract: SUMMARY A large-scale model of the coronary circulation, instrumented to permit detailed pressure and velocity measurements, has been used to study flow through isolated stenotic elements in large coronary arteries. Pulsatile aortic pressure and instantaneous peripheral resistance were simulated with servo valves. A variety of axisymmetric and asymmetric stenoses were studied and flow separation was found to occur for all but very mild stenoses. Pressure recovery downstream of the stenosis throat was limited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1

Year Published

1980
1980
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(60 citation statements)
references
References 16 publications
6
53
1
Order By: Relevance
“…This did not occur with angiotensin II which is rapidly metabolized by intrarenal enzymes (Oparil & Bailie, 1973). The resistance to blood flow exerted by a fixed-diameter arterial stenosis is not constant but varies with arterial pressure and distal vascular resistance (Anderson et al 1979a;Gould et al 1974;Mates et al 1978;May et al 1963;Schwartz et al 1979;Walinsky et al 1979;Young et al 1977). In all groups in the present study, the calculated stenosis resistance fell from its initial value over the hour of stenosis.…”
Section: Discussionmentioning
confidence: 44%
“…This did not occur with angiotensin II which is rapidly metabolized by intrarenal enzymes (Oparil & Bailie, 1973). The resistance to blood flow exerted by a fixed-diameter arterial stenosis is not constant but varies with arterial pressure and distal vascular resistance (Anderson et al 1979a;Gould et al 1974;Mates et al 1978;May et al 1963;Schwartz et al 1979;Walinsky et al 1979;Young et al 1977). In all groups in the present study, the calculated stenosis resistance fell from its initial value over the hour of stenosis.…”
Section: Discussionmentioning
confidence: 44%
“…Intrastenotic flow for most coronary stenoses is therefore likely to be underdeveloped, with parabolically shaped velocity profiles being approached only with very long stenoses, under resting flow conditions. For such flow conditions, viscous losses across coronary stenoses would be greater than that predicted by the presently used equations (Seeley and Young, 1976;Iipscomb and Hooten, 1978), as would the inertial expansion losses as previously hypothesized (Mates et al, 1978;Lipscomb and Hooten, 1978). Entrance losses, previously assumed to be negligible in quantitative arteriography, are related to the issue of flow profile effects, since entrance geometry may profoundly affect flow profiles in the stenotic segment and therefore influence exit losses as well.…”
Section: Relation Between Anatomic and Functional Characteristics Of mentioning
confidence: 74%
“…According to presently used fluid dynamic equations for flow in rigid tubes (Young andTsai, 1973a, 1973b;Brown et al, 1977;Mates et al, 1978;lipscomb and Hooten, 1978;Gould, 1978a;Gould et al, 1982), the energy or pressure losses across a coronary artery stenosis occur primarily because of two geometric characteristics: narrowness of the arterial lumen and its abrupt expansion at the distal end where it opens into the normal-sized artery. Along the narrowed lumen of the stenosis, viscous friction is generated by the layers of blood sliding against each other and against the endothelium of the artery.…”
Section: Principles Of Fluid Dynamics In Narrowed Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In videodensitometry, the concentration of the contrast medium at the objective site to be measured is converted to the intensity of videosignals, and the concentration of the contrast medium can be considered to reflect the cross-sectional area of the lumen of the coronary artery rather than the luminal diameter.6)-8) The luminal cross-sectional area is well known to be a major determinant of coronary flow, and is clinically more important than the luminal diameter.4), 9) In the present study, the intraobserver variability in videodensitometry was found to be small. The results obtained by 2 observers were almost iden- tical, indicating that interobserver variability is also minimum.…”
Section: Discussionmentioning
confidence: 99%